1990
DOI: 10.1073/pnas.87.11.4058
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic stimulation of human tumor-infiltrating lymphocytes by secreted factor(s) from human tumor cell lines.

Abstract: Tumor-infiltrating lymphocytes (TILs) have shown in vivo antitumor efficacy in both animal and human studies. Functions thought necessary for antitumor activity include cytolysis, homing, and proliferation at tumor sites. TILs, which are T lymphocytes grown ex vivo directly from tumors, bear interleukin 2 (IL-2) receptors capable of transducing the IL-2 mitogenic signal. However, IL-2 is not normally synthesized by solid tumor cells. This study was aimed at exploring the possible presence of T-cell mitogens of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It is, therefore, possible that this and/or other cytokines secreted by the neoplastic cell population may play a part in the stimulation of NK cell secretory activity at the tumour site. They may also play a part in the mitogenic stimulation of lymphocytes by tumour cell lines recently reported by Packard (1990).…”
Section: Resultsmentioning
confidence: 88%
“…It is, therefore, possible that this and/or other cytokines secreted by the neoplastic cell population may play a part in the stimulation of NK cell secretory activity at the tumour site. They may also play a part in the mitogenic stimulation of lymphocytes by tumour cell lines recently reported by Packard (1990).…”
Section: Resultsmentioning
confidence: 88%
“…In the past, hollow -fiber bioreacto rs have been used for productio n of industrial and clinical-g rade reagents such as monoclonal antibodies (Knight, 1989;Roggenbuck et al, 1995;Inoue et al, 1996), expansion of infusible cells (Knazek et al, 1990;Packard, 1990;Freedm an et al, 1994), and other biologics destined for pharm acologica l applicati ons (Bano et al, 1985;Liu et al, 1987;Liu et al, 1991). An ACS available commercially (Cellco Division, Spectrum Laboratorie s, Lagura Hills, CA) would provide the potential advantage s of introducing a fixed pericellul ar environm ent and accomm odating a relatively large quantity of cells at high cell density; in fact, tum or-infiltr ating lym phocytes have been grow n in this system (Knazek et al, 1990).…”
Section: Introduction P Er Ip H Er a L B Lo O D Ly M Ph O C Y Tes (Pbmentioning
confidence: 99%
“…The application of a hollow‐fiber bioreactor system (HBS) may provide a solution for many of the difficulties associated with hematopoietic stem cell gene transfer. In the past, such systems have been used for production of industrial and clinical‐grade reagents such as monoclonal antibodies 24, cell lines 25, 26, and other biologics destined for pharmacological applications 27, 28. In our previous work 29, we have demonstrated that an HBS could be used to culture and transduce human primary peripheral blood lymphocytes (PBL) in clinically useful quantities (up to 10 10 primary PBL).…”
Section: Introductionmentioning
confidence: 99%